Safety of conscious sedation in electroanatomical mapping procedures and cryoballoon pulmonary vein isolation - Weinmann, Karolina (Heart Vessels, 2020)
Immobilization of patients during electrophysiological procedures, to avoid complications by patients’ unexpected bodily motion, is achieved by moderate to deep conscious sedation using benzodiazepines and propofol for sedation and opioids for analgesia. Our aim was to compare respiratory and hemodynamic safety endpoints of cryoballoon pulmonary vein isolation (PVI) and electroanatomical mapping (EAM) procedures. Included patients underwent either cryoballoon PVI or EAM procedures. Sedation monitoring included non-invasive blood pressure measurements, transcutaneous oxygen saturation (tSpO(2)) and transcutaneous carbon-dioxide (tpCO(2)) measurements. We enrolled 125 consecutive patients, 67 patients underwent cryoballoon atrial fibrillation ablation and 58 patients had an EAM and radiofrequency ablation procedure. Mean procedure duration of EAM procedures was significantly longer (p < 0.001) and propofol doses as well as morphine equivalent doses of administered opioids were significantly higher in EAM patients compared to cryoballoon patients (p < 0.001). Cryoballoon patients display higher tpCO(2) levels compared to EAM patients at 30 min (cryoballoon: 51.1 ± 7.0 mmHg vs. EAM: 48.6 ± 6.2 mmHg, p = 0.009) and at 60 min (cryoballoon: 51.4 ± 7.3 mmHg vs. EAM: 48.9 ± 6.6 mmHg, p = 0.07) procedure duration. Mean arterial pressure was significantly higher after 60 min (cryoballoon: 84.7 ± 16.7 mmHg vs. EAM: 76.7 ± 13.3 mmHg, p = 0.017) in cryoballoon PVI compared to EAM procedures. Regarding respiratory and hemodynamic safety endpoints, no significant difference was detected regarding hypercapnia, hypoxia and episodes of hypotension. Despite longer procedure duration and deeper sedation requirement, conscious sedation in EAM procedures appears to be as safe as conscious sedation in cryoballoon ablation procedures regarding hemodynamic and respiratory safety endpoints.